ETHICAL SPACES - MÉMETEAU, Gérard (MEDECINE LEGALE DROIT MEDICAL, 2025)
At first, ethics committees were spontaneous and local, but they have since become regulatory, although they are multiplying. We have the “spaces” resulting from these sources. Experience has shown them to be a rich source of reection, but still discreet.